Hubungan Dukungan Keluarga Dengan Tindakan Penderita Tb Paru Melakukan Kontrol Ulang Di Puskesmas Sidomulyo - Khoirul Amin Subhakti; Arneliwati - -; Erwin - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research purpose to know how the relationship of supported family with psychomotor from patient tuberculosis of the lungs to control repeated in Sidomulyo’s Puskesmas. This research use a correlative description method and use cross sectional curses. The sample are 41 respondens that taken use purposive sampling technique. The tool used for this research was a quationaire with 27 statements. An analysis is bivariate analysis using Chi square test. The result of this research showed that 95,7% respondens from positive supported family and routine control. Then respondens with positive supported family and doesn’t routine control that 4,3%. And then result from negative supported family and respondens routine control that 50.0%. As soon as respondens have negative supported family and doesn’t routine control that 50,0%. The result of statistics that P value = 0,001 < α = 0,05 is relationship between supported family and psychomotor from tuberculosis of the lungs to control repeated in Sidomulyo’s Puskesmas.   Keywords: supported family, psychomotor, patient tuberculosis of the lungs, control repeated